Structure, stability and mechanical performance of AlN: ag nanocomposite films - Lotsari, A.; Dimitrakopulos, George P.; Koutsokeras, Loukas E.; Kehagias, Thomas; Kavouras, Panagiotis; Zoubos, Harrisis; Patsalas, Panos A.; Komninou, Philomela (My University, 2010)
Nanocomposite films consisting of a hard AlN matrix incorporating soft Ag inclusions (AlN:Ag) and which are suitable for protective coatings are presented. The growth has been performed using Pulsed Laser Deposition and the film structural properties, such as nanoparticle size and distribution, were studied in relation to the growth parameters, such as metal content and PLD working pressure and laser power. High resolution transmission electron microscopy and nanoindentation were employed in order to determine the film composition, inclusions' crystal structure and mechanical properties respectively. The employed Ag nanoparticles had average sizes ranging between 3–10 nm and were clearly separated by the matrix material. The critical parameters, which determine the nanoparticle size and distribution, and the decisive role of the latter on the mechanical performance of AlN:Ag nanocomposite films are established
Keywords: Εlectron microscopy; Μechanical properties; Νitrides; Laser deposition; Nanocomposites